The need for assisted reproductive technology regulations: a case for women in the Philippines - Biana, Hazel T. (Frontiers in Sociology, 2025)
No laws regulate Assisted Reproductive Technology (ART) in the Philippines. Because of this, women who suffer from infertility must settle with specific guidelines crafted by medical and fertility specialists and professional organizations. As a result, women have limited access to ART and rely on scarce healthcare services and facilities, which may be at the mercy of several guidelines influenced by personal and religious beliefs. In this essay, I examine these regulations (or lack thereof), their socio-cultural motivations, and their dire implications on women and their reproductive rights. I show that Philippine ART regulations lag compared to some developing countries; women have limited choices to address their fertility and reproductive health issues, and they lack the support that they need in dealing with infertility. Thus, regulations need to be crafted to make ART practices more inclusive and less inhibiting for women in the Philippines.